RE-DESIGN OF ADDITIVE MANUFACTURED SPARE PARTS BASED ON FEATURES CLASSIFICATION. (May 2020) - Montero, J.; Weber, S.; Bleckmann, M.; Paetzold, K.
Abstract: Additive Manufacturing is doing its first steps in the production of spare parts. Usually the spares belong to legacy systems, and the tooling to produce them is no longer available. Re-designing spares that are designed for a previous industry mindset can be sometimes challenging. In this study a rather classic design approach is compared to a functional driven approach. Four case studies from different clients are reported, remarking the benefits and drawbacks of using design for additive manufacturing practices in Laser Powder Bed Fusion.